Uplink Multiple Access for Reconfigurable Intelligent Surface-Aided Wireless Systems. (21st July 2022) - Nguyen, Nhan Duc; Le, Chi-Bao; Munochiveyi, Munyaradzi
Abstract : The integration of reconfigurable intelligent surface- (RIS-) aided wireless communication and multiple access is an attractive and promising scheme for next-generation wireless networks. In this research work, separate uplink RIS-aided nonorthogonal multiple access (NOMA) and uplink relay-assisted NOMA schemes are studied, where the RIS and relay devices are deployed to enhance the coverage of an obstructed single-antenna far user by assisting it to communicate with a single-antenna base station. In each scenario, both perfect successive interference cancellation (pSIC) and imperfect successive interference cancellation (ipSIC) operations are considered in the proposed multiple access network. To characterize the system performance, the associated residual interference caused by ipSIC and relay loop self-interference is characterized using the Rayleigh fading model; subsequently, new channel statistics are derived based on the Gauss-Laguerre polynomial. Consequently, the closed-form approximate outage probability expressions are derived for each scenario in the high signal-to-noise ratio (SNR) regime. To gain further insight, the system throughput in the delay-limited transmission is also obtained for each scenario. The formulated expressions are validated via Monte-Carlo simulations. Finally, the obtained simulation results demonstrate and validate the superiority of the RIS system over the relay device under several system parameters of interest despite the limitation of ipSIC.